2010
DOI: 10.1002/jsfa.3910
|View full text |Cite
|
Sign up to set email alerts
|

Fruit physical, chemical and aromatic attributes of early, intermediate and late apricot cultivars

Abstract: In apricot, detailed analysis of the aromatic profile may represent an efficient tool for classification of genotypes by ripening season, and volatiles with relevant odour contribution may serve as quality markers for selecting towards an extended ripening season of best quality apricots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
44
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 51 publications
10
44
2
2
Order By: Relevance
“…The total antioxidant capacity of this fruit has been measured, especially in the hydrophilic fruit extracts, which mainly contain polyphenols and vitamins. Many phenols have been identified in apricots [8,15,16] that are also known to be a rich source of carotenoids, which are important compounds for the eyes and skin. Recent investigations of the antioxidative effect of carotenes such as phytoene and phytofluene have suggested that they may be part of the oxidative stress defence system in human tissues [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The total antioxidant capacity of this fruit has been measured, especially in the hydrophilic fruit extracts, which mainly contain polyphenols and vitamins. Many phenols have been identified in apricots [8,15,16] that are also known to be a rich source of carotenoids, which are important compounds for the eyes and skin. Recent investigations of the antioxidative effect of carotenes such as phytoene and phytofluene have suggested that they may be part of the oxidative stress defence system in human tissues [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…regions of the world have been carried out and studied by many researchers (Greger and Schieberle, 2007;Lo Bianco et al, 2010;Xi et al, 2016). Ethyl acetate, hexyl acetate, limonene, 6-methyl-5-hepten-2-one, menthone, E-hexen-2-al, linalool, bionone and c-decalactone have been determined as important aromatic components in apricot (Guichard and Souty, 1988;Takeoka et al, 1990;Guillot et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…2). Similarly somewhat, pulp volatiles measured by headspace solid phase micro extraction (HS-SPME) followed by gas chromatography/mass spectrometry (GC/MS) are related to fruit harvest seasons in apricot (Prunus armeniaca L.) samples (Bianco et al, 2010). Pulp volatiles of measured by …”
Section: B Amentioning
confidence: 99%